Análise de estabilidade de falésias na zona costeira de Baía Formosa - RN - Souza Júnior, Carlos de (2013)
The natural and anthropogenic changes that are occurring at the coastal zone around the world represent the greatest problem to society in this century. This problem becomes more evident due to high density of coastal cities, to growing tourist-estate speculation of those areas and to climate change that tend to trigger and accelerate the erosive processes that operating in the littoral. In this context, it‟s possible perceive ever more a significant increase of problems associated to the coastal erosion and retreat of cliffs in the state of Rio Grande do Norte, where this study area of this search is located. The area is located in the coastal zone of the city of Baía Formosa/RN, in south-eastern coast of Rio Grande do Norte, and has a extension of about 1200 meters along the Porto beach. The main objective of this study is to analyze the stability of these cliffs in this region. Through field investigations, testings and computational analysis using the Finite Element Method and Equilibrium Limit Methods. The area was divided into four sections, and were applied checklists, and also realized characterization tests and direct shear tests with materials obtained along these sections. In this manner, it was found that the segments of cliff in this coastal zone have heights around 4 meters to 14 meters and inclinations of approximately 40° to 90°.However the constituents soils of the cliffs were classified, in general terms in accordance to Unified Soil Classification System (USCS), as clayey sands or silty sands, clays of low plasticity, clayey gravels and poorly graduaded sands. The most variegated and clayey soils belong to base of the cliff. The stability analysis showed that the safety factors ranged in section 01, from 1.92 to 4.93, in the section 02, from 1.00 to 1.43, in the section 03, from 1.36 to 1.75 , and section 04, from 1.00 to 3.64. Thus, the sections 02 and 03 were considered more unstable. However, the section 03 can be considered as the most critical section due to the absence of coastal protection structures and the narrow strip of beach.